A Project Report on Enabling Public Auditability and Data Dynamics for Storage Security in Cloud Computing - HARISH KUMAR, SRIKANTH M and MANJUNATH H (2011)
INTERNAL GUIDE: SHIVAGAMASUNDARI, MVJCE
Keywords: Cloud Computing